THE ROLE OF SPIRITUAL PRACTICES ON SOCIAL MEDIA USE FOR GENERATION Z - purbiyati, yuliana sri; Amelia, Luna (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study examines the role of spiritual practices among Generation Z in their use of social media. The study used a qualitative approach, collecting data through interviews with informants consisting of nine religious education teachers and 20 high school students. The research questions were distributed through Google Forms. The study findings revealed that spiritual practices, including prayer, meditation, and reflective writing, contribute to the development of positive emotions, positive behaviors, and positive social relationships among Generation Z. The development of these three aspects influences their decisions regarding social media use. Positive emotions foster positive behaviors, which in turn influence how Generation Z interacts with others in a positive way. This study offers practical implications for teachers in mentoring Generation Z and for Generation Z themselves, especially in making decisions about social media use. Future research is needed to further explore the role of spiritual practices among Generation Z in their use of social media to provide new insights into the role of spiritual practices in shaping the next generation.